2017
DOI: 10.1016/j.rbmo.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative live birth rate following elective single blastocyst transfer compared with double blastocyst transfer in women aged 40 years and over

Abstract: This retrospective cohort study aimed to identify predictive factors for live birth following blastocyst transfer in women aged 40-43, and to compare the cumulative live birth rate (LBR) following elective single blastocyst (eSBT) and double blastocyst (DBT) transfer. The study included 411 women who had fresh blastocyst transfers on day 5. In stepwise logistic regression, independent predictive factors for live birth were: transferring fully expanded blastocysts (Gardner stage ≥3) (odds ratio [OR] 3.5, 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
5
18
0
Order By: Relevance
“…Our results suggested that SBT also appeared to be a promising option that did not compromise the LBR for women over the age of 35 years with available good-quality blastocysts. Moreover, recent studies also indicated that the practice of selective SBT was feasible and resulted in reduced MPRs in women aged 40–43 years without compromising cumulative LBR compared with DBT [ 9 , 10 ], suggesting that maternal age was not a significant predictor of live birth, and the competence of the oocytes developing into good-quality blastocysts is more important than maternal age (10). Additionally, another study reported that maternal age has no effect on pregnancy rates when fully expanded blastocysts are achieved [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggested that SBT also appeared to be a promising option that did not compromise the LBR for women over the age of 35 years with available good-quality blastocysts. Moreover, recent studies also indicated that the practice of selective SBT was feasible and resulted in reduced MPRs in women aged 40–43 years without compromising cumulative LBR compared with DBT [ 9 , 10 ], suggesting that maternal age was not a significant predictor of live birth, and the competence of the oocytes developing into good-quality blastocysts is more important than maternal age (10). Additionally, another study reported that maternal age has no effect on pregnancy rates when fully expanded blastocysts are achieved [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that multiple pregnancies are associated with a higher risk of neonatal and perinatal complications [ 10 ]. Our results consisted of the aforementioned conclusion, showing that 70–90% of preterm births resulted from multiple pregnancies, and about 85–95% of low birth weight babies come from multiple pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear de nition of selective SBT was given in a study [9], namely, a single blastocyst was transferred and at least one blastocyst was available for cryopreservation. However, the detailed grading of transferred embryos for eSBT and DBT in these studies was not clearly described [7,10,11]. The quality of the blastocysts transferred in the DBT group met the conditions of one of three scenarios; the two blastocysts may have been both of good-quality, of averagequality or a combination of one good-and one average-quality blastocyst.…”
Section: Introductionmentioning
confidence: 95%
“…16 Transferring more embryos will increase the chances of a pregnancy, but is likely to result in twins or higher-order births. 17 Multiple birth is significantly more dangerous for the mother, with a high risk of complications and potential need for cesarean section delivery. 18 Other physical risks of IVF include side effects of hormonal treatment, ovarian hyperstimulation syndrome during pre-treatment for egg retrieval, 19 infection from retrieval or transfer procedures, 20 and risks associated with pregnancy and delivery especially for older mothers.…”
mentioning
confidence: 99%